2020
DOI: 10.1515/tnsci-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Decreased MiR-30a promotes TGF-β1-mediated arachnoid fibrosis in post-hemorrhagic hydrocephalus

Abstract: AbstractBackgroundFibrosis in the ventricular system is closely associated with post-hemorrhagic hydrocephalus (PHH). It is characterized by an expansion of the cerebral ventricles due to CSF accumulation following intraventricular hemorrhage (IVH). The activation of transforming growth factor-β1 (TGF-β1) may be involved in thrombin-induced arachnoid fibrosis.MethodsA rat model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Researchers tried to interfere with the TGF‐β pathway as a means to treat hydrocephalus in animal models 59,60 . Manaenko et al administered SD208, a TGF receptor I inhibitor, daily for 3 days after GMH induction and compared the result with vehicle‐treated GMH rats.…”
Section: Antifibrotic Treatment For Hydrocephalusmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers tried to interfere with the TGF‐β pathway as a means to treat hydrocephalus in animal models 59,60 . Manaenko et al administered SD208, a TGF receptor I inhibitor, daily for 3 days after GMH induction and compared the result with vehicle‐treated GMH rats.…”
Section: Antifibrotic Treatment For Hydrocephalusmentioning
confidence: 99%
“…Researchers tried to interfere with the TGF‐β pathway as a means to treat hydrocephalus in animal models. 59 , 60 Manaenko et al administered SD208, a TGF receptor I inhibitor, daily for 3 days after GMH induction and compared the result with vehicle‐treated GMH rats. The results showed that high‐dose SD208 inhibited GMH‐induced activation of the TGF‐β pathway, reduced the deposition of vitronectin, and alleviated brain atrophy and hydrocephalus.…”
Section: Antifibrotic Treatment For Hydrocephalusmentioning
confidence: 99%
“…Because NPH is frequently detected in people with Alzheimer’s disease, the current hypothesis proposes that NPH is the outcome of neurodegenerative alterations in AD patients. The removal of toxic molecules such as Aβ is aided by the circulation of CSF ( Zhan et al, 2020 ).…”
Section: Factors Causing Pathophysiology Of Motile Cilia In Hydroceph...mentioning
confidence: 99%
“…Preoperative MRI cerebrospinal uid ow imaging will be added to patients in our department to observe whether the base of the third ventricle is bulging downward or sagging and whether the ow of cerebrospinal uid in the mesencephalic aqueduct is unobstructed to aid in differentiation [29]. For patients with typical symptoms of normal pressure hydrocephalus, our department performs a preoperative cerebrospinal uid tap test to assess the prognosis of the patient, whose speci c operation is to administer a single dose of 40-60ml of cerebrospinal uid at a single time and observe the improvement of the patient's symptoms 24-48 hours after the uid release [33]. According to the Japanese Neurosurgical Association's guidelines for the management of idiopathic normal pressure hydrocephalus (NPH) [16] and the American Idiopathic NPH Study Group's guidelines [20], the positive predictive value of the uid release test is 73%-100%.…”
Section: Surgical Proceduresmentioning
confidence: 99%